Questioning Sustainable Environmental Policies and Practices in Indonesia: Would Durkheim’s Structural Functionalism Theory Have a Relevance? - Wijaya, I Made Marta; Sudaryanto, Agus (Udayana Journal of Law and Culture; Vol 8 No 2 (2024)DO - 10.24843/UJLC.2024.v08.i02.p03, 2024)
Indonesia, as a signatory to the UNFCCC and the Paris Agreement, is committed to reducing greenhouse gas (GHG) emissions. These commitments, outlined in Law Number 16 of 2016, include limiting global temperature rise, setting Nationally Determined Contributions (NDC) targets, and developing a long-term strategy for net zero emissions by 2050. To meet these obligations, the Indonesian government has introduced Carbon Economic Value (CEV) policies through Presidential Regulation Number 98 of 2021. These policies aim to reduce GHG emissions by implementing carbon pricing mechanisms such as carbon trading, levies, and performance-based payments. However, the implementation of CEV policies has faced various reactions, including criticism and resistance. Despite these challenges, it's imperative not to hinder the policy's implementation, given its potential to drive significant societal and lifestyle changes towards a greener future. This study analyzes Indonesia's progress in reducing GHG emissions through CEV policies. Using normative legal research and qualitative analysis, it explores the positive impacts of these policies, including their alignment with structural functionalism theory. The study highlights that the implementation of CEV policies as an effort to reduce greenhouse gas emissions in Indonesia through carbon trading mechanisms, carbon taxes, and funding partnerships with developed countries aligns with structural functionalism theory according to Emile Durkheim. This is evidenced by the existence of a clear system (legal and governance) in implementing CEV policies, including regulators (Government), implementers (SOEs, private sector, and society), supervisors (UNFCCC), and program donors (World Bank, IMF), where each entity cooperates in an organized manner in accordance with the provisions of the Paris Agreement 2015 and Presidential Regulation 98 of 2021 continuously according to their respective tasks. This policy also brings about functional social change by promoting a harmonious balance to shift dependence away from fossil fuels towards more environmentally friendly Renewable Energy sources.